Inflammatory bowel disease diagnosis and therapeutics - Cohen, Russell D. (New Jersey Humana Totowa, 2011)
This Second Edition of Inflammatory Bowel Disease: Diagnosis and Therapeutics, provides readers with the most up-to-date approaches to IBD states, expansion of biological agents of treatment, new studies in the epidemiology of IBD, the changing economics of IBD, major advances in novel readiographic techniques; which aid in the detection of colorectal cancer in patients with IBD and new findings in the genetics of IBD. Major breakthroughs in new endoscopic evaluations of the bowel (i.e. Capsule endoscopy, double-balloon enteroscopy, endoscopic ultrasound) and their use in the inflammatory bowel diseases is also summarized in this book. This new edition continues to provide readers with a concise, yet in-depth review of many of the important areas in history, epidemiology, pathogenesis, diagnosis, and treatment of the inflammatory bowel diseases (ulcerative colitis and Crohn's disease), as well as associated issues: extra intestinal manifestations, ostomy care, women's issues and economics.
The influence of twentieth-century biomedical thought on the origins of inflammatory bowel disease therapy / Joseph B. Kirsner -- The changing epidemiology of IBD / Anders Ekbom -- Recent advances in the genetics of IBD / Russell D. Cohen -- New paradigms in the pathogenesis of IBD / Giorgos Bamias, Theresa Pizarro, and Fabio Cominelli -- State of the art medical treatment of the adult patient with IBD : the mesalamine-based therapies / L. Campbell Levy and Corey A. Siegel -- State of the art medical treatment of the adult patient with IBD : modern use of corticosteroids / Wojciech Blonski, David Kotlyar, and Gary R. Lichtenstein -- State-of-the-art medical therapy of the adult patient with IBD : the immunomodulators / Dana Moffatt and Charles N. Bernstein -- State-of-the-art medical treatment of the adult patient with IBD : the biological therapies / Stephen B. Hanauer -- Prebiotics, probiotics, antibiotics, and nutritional therapies in IBD / Richard N. Fedorak, Levinus A. Dieleman, and Karen L. Madsen -- State-of-the-art management of the pediatric IBD patient / Marla Dubinsky -- Innovations in the surgical treatment of inflammatory bowel disease / Roger Hurst -- Clinical utility of serological markers and thiopurine drug monitoring in IBD : an evidence-based review / Raja Tamaz and Ernest G. Seidman -- Caring for women with inflammatory bowel disease / Sunanda Kane and Rebecca Kowalczyk -- Novel radiographic techniques in IBD patients / V. Anik Sahni and Koenraad J. Mortele -- Novel techniques in the diagnosis of inflammatory bowel disease / Shabana F. Pasha and Jonathan A. Leighton -- Inflammatory bowel disease pathology slideshow / Christopher R. Weber -- New findings in the diagnosis and prevention of colorectal cancer in IBD / David T. Rubin and Jami A. Rothe -- Managing the patient with a fecal diversion / Janice C. Colwell -- The new economic reality in the world of IBD / Nanda Venu and Russell D. Cohen.
Electronic reproduction.
Keywords: Inflammatory bowel diseases -- Diagnosis; Inflammatory bowel diseases -- Treatment